Perancangan Webseries Wisata Budaya Kampung Adat Cikondang Bersama Bobobox Dalam Meningkatkan Awarness Untuk Generasi Z - Irham Ghani Rizki; I Gusti Agung Rangga Lawe; Aisyi Syafikarani (Universitas Telkom, 2024)
Tourist destinations that implement sustainable tourism, provide education, and empower local communities have a greaterappeal to tourists. One example is visiting cultural village tourism, where visitors can enjoy local life and culture, gainingunforgettable experiences. In West Java, there are several cultural village tourism sites that preserve Sundanese culturalheritage well, such as Lamajang Village in Pangalengan. The natural and cultural potential of Lamajang Village in Pangalengan needs to be optimally utilized to attract tourists. One such potential is Kampung Adat Cikondang, which preservesancestral customs and offers an experience of traditional Sundanese community life from the past. However, the main challenge currently faced is the lack of awareness and knowledge among tourists about this cultural village, hindering its visitorpotential. To address this issue, a promotional strategy needs to be designed along with the appropriate media selectionto ensure visitors receive information that increases the number of visitors to Kampung Adat Cikondang. To support thisdesign, qualitative research methods will be employed, including data collection through observation, interviews, and questionnaires. Several analytical methods such as SWOT analysis, 4A analysis, AOI analysis, AISAS and Matrix analysis willbe used to formulate the promotional media design. A webseries video commercial will be chosen as the primary media,supported by other media to strengthen the campaign and enhance awareness of Kampung Adat Cikondang.